Migration, Political Institutions, and Social Networks - Catia Batista; Julia Seither; Pedro C. Vicente (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2018)
What is the role of international migrants and, specifically, migrant networks in shaping political attitudes and behavior in migrant sending countries? Our theoretical framework proposes that migration might change individual social identities and thus stimulate intrinsic motivation for political participation, while it may also improve knowledge about better quality political institutions. Hence, international migration might increase political awareness and participation both by migrants and by other individuals in their networks. To test this hypothesis, we use detailed data on different migrant networks (geographic, kinship, and chatting networks), as well as several different measures of political participation and electoral knowledge (self-reports, behavioral, and actual voting measures). These data were purposely collected around the time of the 2009 elections in Mozambique, a country with substantial emigration to neighboring countries - especially South Africa - and with one of the lowest political participation rates in the region. The empirical results show that the number of migrants an individual is in close contact with via regular chatting significantly increases political participation of residents in that village - more so than family links to migrants. Our findings are consistent with both improved knowledge about political processes and increased intrinsic motivation for political participation being transmitted through migrant networks. These results are robust to controlling for self-selection into migration as well as endogenous network formation. Our work is relevant for the many contexts of South-South migration where both countries of origin and destination are recent democracies. It shows that even in this context there may be domestic gains arising from international emigration.
Keywords: D72; D83; F22; O15; 330; International migration; social networks; political participation; information; diffusion of political norms; governance